Determinants of academic adaptation and quality of life of university students in the Brazilian Amazon region - Oliveira Silva, George; Carneiro, Priscilla Rodrigues Caminha; Aredes, Natália Del Angelo; do Nascimento, Ladislau Ribeiro (Frontiers in Education, 2025)
This study aimed to identify the determinants of academic adaptation and quality of life in university students. Through a cross-sectional design, 90 university students participated in the research, responding to a questionnaire focused on sociodemographic, academic, and health-related variables. The Academic Life-Experiences Questionnaire and the Medical Outcomes Study 36-Item Short-Form Health Survey were used to evaluate academic adaptation and quality of life, respectively. Multiple linear regressions were performed to identify positive and negative predictors of these outcomes. The results showed that high scores in the physical and mental components of quality of life, living in the same city as the university, and receiving some types of scholarship were positive predictors of academic adaptation, while not performing physical activities was a negative predictor. The positive predictors of the physical component were income of more than two minimum wages, having no comorbidities, and being students of Black race. In contrast, the negative predictors were stressful factors such as the teaching method, evaluation method, and experiences during the internship. The mental component had only positive predictors, such as having no intention of dropping out and having no minor mental disorders. Academic adaptation was positively correlated with physical and mental components of quality of life. The findings of this study showed that university students’ academic trajectories have diverse influencing factors related to sociodemographic, academic, and health-related determinants.